EVALUATION OF CARDIOPROTECTIVE ACTIVITY OF AQUEOUS EXTRACT OF GARCINIA INDICA LINN FRUIT RIND - Hegde, Karunakar; Patel, Dhruv Kamlesh Kumar; Varma, Keerthi (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: To evaluate Cardioprotective activity of aqueous extract of Garcinia indica Linn fruit rinds. Methods: Wistar rats were divided into different groups. Two doses 250 mg/kg and 500 mg/kg b.w, p.o of the Garcinia indica fruit rind extract (GIFE) were subjected for the evaluation of Cardioprotective activity against Isoproterenol (ISO) and Ischemia reperfusion injury (IRI) induced myocardial damage in rats. Propranolol (10 mg/kg b.w, p.o) was used as a standard drug. The influence of prophylactic treatment was analysed by quantification of biomarkers and antioxidants, physical parameters and histopathological observations. Results: Both GIFE-250 and GIFE-500 showed significant reduction in CK-MB, CK-NAC, LDH in the extract treated rats when compared with positive control. Both the doses showed increase in SOD and CAT levels. Significant level of percentage recovery in terms of heart rate and developed tension were seen in all treated groups in IRI model. Cardioprotective effect was also confirmed by histopathology of hearts which showed less necrosis in extract treated rats when compared to untreated rats of toxic control group. The results obtained were comparable with that of the standard. Thus investigational finding conclude that, the administration of high dose of GIFE was the most effective in alleviating the abnormal conditions induced by Isoproterenol and Ischemia reperfusion. Conclusion: The present study concluded that Garcinia indica Linn fruit rinds were found to be effective against Isoproterenol (ISO) and Ischemia reperfusion (IR) induced myocardial damage in rats. Keywords: Cardioprotective, Garcinia indica,Ischemia reperfusion injury, Isoproterenol, Propranolol